PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KETEPATWAKTUAN PENYAMPAIAN LAPORAN KEUANGAN DAN IMPLIKASINYA PADA EARNING RESPONSE COEFFICIENT - Dewi, I Gusti Ayu Ratih Permata; Yadnyana, I Ketut; Sudana, I Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aims to examine the effect of profitability and size of the company and the timeliness of financial reporting implications on earnings response coefficient Indonesian companies, especially manufacturing companies. The data used is secondary data in the external form of financial statements and annual reports of companies listed on the Indonesia Stock Exchange in 2012-2014. Selection of the sample with purposive sampling method and acquired 76 companies with the number of observations for 3 years. Data analysis technique used is path analysis (path analysis). The test results showed that the profitability and size of the company positive impact on the timeliness of financial reporting. Profitability negative effect on earnings response coefficient and size of the company's positive effect on earnings response coefficient. Further timeliness of submission of financial statements to mediate the effect of profitability and the size of the company on earnings response coefficient.
Keywords: profitability, company size, timeliness, earning response coefficient